A 2000 Social Accounting Matrix (SAM) for the Slovak Republic - Koronczi, Karol (International Food Policy Research Institute, 2005)
Slovak Republic is in process of transformation from a centrally planned to a market economy. It is a process that requires constant development and adjustment of various systems, including the national statistics. Integration into the European Union (EU) evokes the need to standardize the system of national accounts with those utilized in other EU countries. This work attempts to provide a Social Accounting Matrix (SAM) for the Slovak Republic for the year 2000. A SAM is an excellent descriptive tool, showing in detail the structure of an existing national economy. It provides important information on individual industrial sector size, behavior, and interaction with the rest of the economy, and a link with the foreign world. It is a necessary tool for Computable General Equilibrium (CGE) modeling. Data construction in this work generally follows the standard procedures suggested by the United Nations and Eurostat. The process in particular transforms Supply and Use tables into a symmetric Input-Output table, and once again, it is transformed into the symmetric SAM. This paper discusses the organization, methodology, arrangement and estimation of data and constructs a detailed SAM, extended by additional macroeconomic data, such as Labor Supply or Stocks of Fixed Capital.